To design a high speed Hadamard transform block using in the digital signal processing systems - Do, Xuân Tiến; Hoang, Thị Phương (Journal of Technical Education Science, 2014)
In the digital signal processing systems such as withholding information system on sound data, images are treated as information security measures are effective and feasible for the copyright protection. In traditional scheme of hiding information systems the Hadamard transform block is used more for its simplicity and orthogonality of this algorithm. This paper presents a design methodology of the high speed Hadamard transform block through a combination held simultaneously between hardware and software at the core level of ALU system architecture helps accomplish multiple tasks in parallel so speed implementation of algorithm is very high.